Analisis Pendapatan Petani Padi Sawah di Kecamatan Balinggi Kabupaten Parigi Moutong Sulawesi Tengah - Safitri, Dian; Erny, Erny; Kalaba, Yulianti; Alamsyar, Al (MuJAgri: Musamus Journal of Agribusiness, 2024)
Rice, a major food crop that thrives throughout Indonesia, allows you to fulfill your need for food without relying on imports. The objective of this study is to determine the income earned by wet-rice farmers in Balinggi Sub-district, Parigi Moutong District. Expenditures on activities carried out from the provision of means of production to harvesting affect farmers' income. An income analysis will be used, which shows that wet-rice farmers in Balinggi Sub-district earn a low income, amounting to IDR 21,042,084 per growing season for 0.84 ha of land, or IDR 25,124,876 per ha.